RELATIONSHIP BETWEEN PARENTING PATTERNS AND SOCIAL INTERACTION SKILLS OF CHILDREN WITH MENTAL RETARDATION IN SLB ACD PERTIWI KOTA MOJOKERTO - Imam Zainuri; Lilik Ma’rifatul Azizah; Shinta Baron (Suluh Adiluhung Publisher (SAPub), 2025)
Parenting patterns are one of the factors that can affect children's social interaction skills. Social interaction skills are a form of behavior that is very important for children in communicating later with people around them. This study aims to determine the relationship between parenting patterns and children's social interaction skills with mental retardation at SLB ACD – Pertiwi Kota Mojokerto. The research method used is Observational with a Cross-sectional approach. The population in this study were parents and children with mental retardation in elementary, junior high, and high school in SLB ACD – Pertiwi Kota Mojokerto category C totaling 37 people. The sampling technique used was Total Sampling, a sample of 37 people, namely parents and children with mental retardation starting from elementary school, as many as 16 people, junior high school as many as 15 people, and high school as many as 6 people. The instrument in this study used the Parenting Style and Dimensions Questionnaire (PQST) questionnaire to determine parenting patterns and Observational using a questionnaire to determine the social interaction skills of children with mental retardation. The results of the study showed that the majority of parenting patterns applied democratic parenting patterns as many as 34 people (91.89%), and the social interaction abilities of mentally retarded children were in the high category as many as 16 people (43,02%). The data analysis method used Crosstabulation between parenting patterns and the social interaction abilities of mentally retarded children, so it can be concluded that the more democratic the parenting patterns, the higher the social interaction abilities of mentally retarded children. This can be said that there is a relationship between parenting patterns and the social interaction abilities of children with mental retardation at SLB ACD – Pertiwi Kota Mojokerto. Good and appropriate parenting patterns can also improve children's social interaction abilities.